Effect of air-abrasion regimens and fine diamond bur grinding on flexural strength, Weibull modulus and phase transformation of zirconium dioxide - Araujo Michida, Silvia Masae de; Kimpara, Estevao Tomomitsu [UNESP]; Santos, Claudinei dos; Assuncao Souza, Rodrigo Othavio; Bottino, Marco Antonio [UNESP]; Oezcan, Mutlu (Wichtig Publ, 2015)
Purpose: This study evaluated the effect of air abrasion and polishing regimens on the flexural strength of yttrium stabilized polycrystalline tetragonal zirconia (Y-TZP). Methods: From Y-TZP blocks (InCeram 2000 YZ Cubes; Vita Zahnfabrik, Bad Sackingen, Germany) 120 bars (25 mm x 4 mm x 1.2 mm) were obtained according to ISO 6872: 2008 and randomly divided into 4 groups: Group C: (control) without surface treatment (n = 30); Group APA: Air abrasion with aluminum oxide (44 mu m) (n = 30); Group SC: Silica-coating (CoJet, 30 mu m) (n = 30); Group FD: Fine diamond bur (n = 30). Subsequently, all specimens were subjected to 4-point bending test (in distilled water at 37 degrees C) in a universal testing machine (EMIC DL 1000; Sao Jose dos Pinhais, Parana, Brazil); cross-head speed: 0.5 mm/min). The characteristic strength (sigma(0)) of each specimen was obtained from the flexural strength test and evaluated using Weibull analysis. X-ray diffraction analysis was utilized to quantity the monoclinic phase. The surface topography of specimens was analyzed using 3D optical profilometer and scanning electron microscopy (SEM) after surface conditioning methods. The flexural strength data (sigma(4p)) were statistically analyzed by 1-way ANOVA, Tukey test (alpha = 0.05) and Weibull (m = modulus, sigma(0) = characteristic strength) were calculated. Results: The mean +/- standard deviations (MPa) of the groups were as follows: C: 1196.2 +/- 284.2(a); APA: 1369.7 +/- 272.3(a); SC: 1207.1 +/- 229.7(a) and FD: 874.4 +/- 365.4(b). The values (m) and (sigma(0)) were as follows: C: 4.5 and 1308.12; APA: 5.9 and 1477.88; SC: 6.0 and 1300.28; and FD: 2.6 and 985.901, respectively. Conclusions: Air particle abrasion with neither silica nor alumina showed significant difference compared to the control group but grinding with fine diamond bur impaired the flexural strength of the zirconia tested.
Keywords: Air abrasion; Polishing; Flexural strength; Weibull modulus; Phase transformation; Yttria-stabilized tetragonal zirconia